Vision and the experience of built environments: two visual pathways of awareness, attention and embodiment in architecture - Rooney, Kevin Kelley (Kansas State University, 2016)
The unique contribution of Vision and the Experience of Built Environments is its specific investigation into the visual processing system of the mind in relationship with the features of awareness and embodiment during the experience of architecture. Each facet of this investigation reflects the essential ingredients of sensation (the visual system), perception (our awareness), and emotions (our embodiment) respectively as a process for aesthetically experiencing our built environments. In regards to our visual system, it is well established in neuroscience that human vision divides into the central and peripheral fields of view. Central vision extends from the point of gaze (where we are looking) out to about 5° of visual angle (the width of one’s fist at arm’s length), while peripheral vision is the vast remainder of the visual field. These visual fields project to the parvo and magno ganglion cells which process distinctly different types of information from the world around us and project that information to the ventral and dorsal visual streams respectively. Building on the dorsal/ventral stream dichotomy, we can further distinguish between focal processing of central vision and ambient processing of peripheral vision. Thus, our visual processing of, and attention to, objects and scenes depends on how and where these stimuli fall on the retina. Built environments are no exception to these dependencies, specifically in terms of how focal object perception and ambient spatial perception create intellectual and phenomenal experiences respectively with architecture. These two forms of visual processing limit and guide our perception of the built world around us and subsequently our projected and extended embodied interactions with it as manifested in the act of aesthetic experience. By bringing peripheral vision and central vision together in a balanced perspective we will more fully understand that our aesthetic relationship with our built environment is greatly dependent on the dichotomous visual mechanisms of awareness and embodiment.
Keywords: Architecture; Visual cognition; Embodiment; Awareness; Attention; Aesthetics; Aesthetics (0650); Architecture (0729); Cognitive Psychology (0633)